The Relationship Between the Intensity of Watching Netflix Series in English and the Speaking Ability of 3rd Semester English Education Students at Sriwijaya University - Vigo Dikaprio; Eryansyah Eryansyah (Universitas Islam Negeri Palopo, 2025)
This study investigates whether the viewing intensity of English Netflix series correlates with speaking ability among 24 third-semester English Language Education students at Sriwijaya University. Using a quantitative correlational design, data were collected over one semester via a viewing intensity questionnaire and a speaking ability test, and analyzed using Pearson Correlation. The results indicated no significant relationship between viewing intensity and speaking ability (r = 0.123, Sig. = 0.519). The remarkably low coefficient of determination (r2 = 1.51) suggests that variance in speaking ability is almost entirely explained by factors other than the intensity of passive viewing. Consequently, the study concludes that passive viewing of Netflix alone is ineffective as a sole tool for improving speaking ability, and its potential as a language learning medium is only realized when integrated with active learning strategies and productive language tasks.